2008
DOI: 10.1002/mrd.20886
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of glycoside residues of porcine zona pellucida and ooplasm during follicular development and atresia

Abstract: The glycoside residues (glycoconjugates, GC) of the zona pellucida (ZP) glycoproteins are important during the first phases of fecundation. Our aim in this work was to determine the lectin affinity pattern of porcine ZP in order to analyze the changes that take place during: (a) preantral folliculogenesis, (b) the follicular atresia process, and (c) antral growth. Several prepubertal and adult pig ovaries and different sized antral follicles were used. Conventional carbohydrate histochemical techniques and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 45 publications
1
23
2
Order By: Relevance
“…Oocytes released from the canine ovarian cortex constitute a heterogeneous population that includes oocytes proceeding from viable follicles (mainly preantral) at different developmental stages and from atretic follicles. In other species, the three‐dimensional structure of the zona pellucida and its carbohydrate composition has been observed to change during follicular growth and atresia (Calafell, Nogués, Ponsá, Santaló, & Egozcue, ; Familiari, Nottola, Familiari, & Motta, ; Pastor et al., ). In this study, oocyte heterogeneity was expected to cause a high variability in sperm binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Oocytes released from the canine ovarian cortex constitute a heterogeneous population that includes oocytes proceeding from viable follicles (mainly preantral) at different developmental stages and from atretic follicles. In other species, the three‐dimensional structure of the zona pellucida and its carbohydrate composition has been observed to change during follicular growth and atresia (Calafell, Nogués, Ponsá, Santaló, & Egozcue, ; Familiari, Nottola, Familiari, & Motta, ; Pastor et al., ). In this study, oocyte heterogeneity was expected to cause a high variability in sperm binding capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Fucose has been detected in the porcine ZP using Ulex europaeus agglutinin 1 (UEA-I) lectin histochemistry (Song et al, 1999;Pastor et al, Pattern A showed significant differences, with higher values observed in the control group (54.7 ± 1.6%) than in the TALP (15.1 ± 1.2%) and TALP + E (12.2 ± 1.1%) groups (P < 0.001); pattern B showed higher values in the TALP group (61.8 ± 1.6%) than in the TALP + E (35.2 ± 1.6%) and control (43.2 ± 1.6%) groups (P < 0.01); pattern C showed significant differences (P < 0.001), with maximum values observed in the TALP + E group (52.5 ± 1.7%) compared with the TALP (23.1 ± 1.4%) and control (2.1 ± 0.5%) groups. Different letters indicate significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Their molecular structure, carbohydrate-binding properties and biological activities have been covered in detail in several reviews [18][19][20][21][22][23][24][25]. These proteins have been widely used for the detection of carbohydrate in various tissues and organs, e.g., the respiratory system [26][27][28][29], digestive system [30][31][32], and male [33][34][35][36][37] and female [38][39][40] reproductive systems, and in diverse pathological situations [41]. The use of lectins for the histochemical detection of glycans in tissue sections (lectin histochemistry) is an area of important applications for these molecules.…”
Section: Apoptosis and Glycoconjugatesmentioning
confidence: 99%